Odpowiedzialność za produkt niebezpieczny podmiotów dystrybuujących żywność - Trapé, Ilaria (Wydawnictwo Naukowe UAM, 2008)
The main focus of all discussions on product liability has been so far put on producer's liability. Only some recent decisions of the European Court of Justice have pointed out to the possible liability of food distributors whose role in relations with producers as well as consumers has been becoming more and more important. The decision of the ECJ in the case brought against Lidl Italia, which concerned Amaro alle erbe liquor, produced in Germany and distributed by Lidl in Italy, has given rise to some interesting reflections on the liability of different subjects in the agro-food sector, and food distributors in particular. That decision is of major significance because it expressly and unambiguously provides for a possibility of finding a distributor fully liable for the products he has been handling. As a result, in a situation where the complexity of the food chain is increasing, all participants must collaborate in that chain to successfully secure efficient food safety, while individual participants could be held liable only for failure to perform the particular obligations assigned to them and determined on the basis of some functional criterion.

Il dibattito sul danno da prodotto difettoso ha polarizzato l’attenzione sulla responsabilità del produttore, ma alcune recenti sentenze délia Corte di Giustizia hanno spostato i riflettori sul distributore, che tende ad assumere sempre più un ruolo da protagonista sia nei rapporti con il produttore, sia con il consumatore. Una vicenda esplicativa in tal senso è quella che ha ad oggetto VAmaro aile erbe prodotto inGermania e distribuito in Italia dalla Lidl e che offre l'occasione per alcune riflessioni intorno alla responsabilità dei diversi operatori del settore alimentare ed, in particolare, del distributore. La sentenza in commenta è significativa in quanta, pur concernendo una responsabilità di tipo amministrativo, rappresenta una decisa ed inequívoca apertura verso una responsabilità piena del distributore. Pertanto, alla luce délia crescente complessità délia food chain, se è indispensable che gli operatori promuovano tra di loro una cooperazione efficiente al fine di garantiré Papplicazione dei precetti di sicurezza alimentare, nello stesso tempo, ciascuno di essi, in base ad un criterio di tipo funzionale, dovrebbe essere ritenuto responsabile solo dell'omissione degli specifici obblighi che gli competono.
Distributor's liability for defective food products
La responsabilita da prodotto difettoso del distributore di alimenti